Log3(x - 1)+ log3(x -2) =log3(2)

YULIAJUICE YULIAJUICE    3   20.12.2020 16:21    1

Ответы
segrejp segrejp  19.01.2021 16:23

х=3

Объяснение:

Log3(x-1)+Log3(x-2)=Log3(2)

ОДЗ:

х-1>0           x-2>0

x>1               x>2

x∈(2;+∞)

Log3((x-1)(x-2))=Log3(2)

(x-1)(x-2)=2

x²-3x+2=2

x²-3x=0

x(x-3)=0

x1=0 (не подходит под ОДЗ)

х2=3

ПОКАЗАТЬ ОТВЕТЫ
Keranius Keranius  19.01.2021 16:23

x = 3.

Объяснение:

log₃(x - 1) + log₃(x - 2) = log₃2

ОДЗ:

x - 1 > 1;   x > 2;  x ≠ 0;  ⇒ x > 2.

log_{3} \left(\dfrac{(x-1) \cdot (x-2)}{2} \right)=0\\\\ \dfrac{(x-1) \cdot (x-2)}{2} =3^{0} \\\\\dfrac{(x-1) \cdot (x-2)}{2} =1\\\\(x-1) \cdot (x-2)=2\\x^{2} -3x+2=2\\x^{2} -3x+2-2=0\\x^{2} -3x=0\\x(x-3)=0\\x_{1} =0; \: \: x_{2} =3

х₁ = 0 - не удовлетворяет области определения.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра